Biaxial tensile tests of the porcine ascending aorta. Issue 10 (5th July 2016) - Deplano, Valérie; Boufi, Mourad; Boiron, Olivier; Guivier-Curien, Carine; Alimi, Yves; Bertrand, Eric
Abstract: One of the aims of this work is to develop an original custom built biaxial set-up to assess mechanical behavior of soft tissues. Stretch controlled biaxial tensile tests are performed and stereoscopic digital image correlation (SDIC) is implemented to measure the 3D components of the generated displacements. Using this experimental device, the main goal is to investigate the mechanical behavior of porcine ascending aorta in the more general context of human ascending aorta pathologies. The results highlight that (i) SDIC arrangement allows accurate assessment of displacements and so stress strain curves, (ii) porcine ascending aorta has a nearly linear and anisotropic mechanical behavior until 30% of strain, (iii) porcine ascending aorta is stiffer in the circumferential direction than in the longitudinal one, (iv) the material coefficient representing the interaction between the two loading directions is thickness dependent, (v) taking into account the variability of the samples the stress values are independent of the stretch rate in the range of values from 10 −3 to 10 − 1 s − 1 and finally, (vi) unlike other segments of the aorta, 4-month-old pigs ascending aorta is definitely not a relevant model to investigate the mechanical behavior of the human ascending aorta.